ISPC Assessment of Flagship 3: Livestock Feeds and Forages - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
ISPC Assessment of Flagship-3 (Livestock feeds and forages) of the CGIAR Research Program on Livestock Agri-Food System (2017-2022). Flagship 3 (feeds and forages) of the Livestock CRP aims to increase livestock productivity and reduce environmental impacts by identifying, testing, and delivering superior feed and forage strategies and options.